PENGARUH BESAR PINJAMAN, DAN JANGKA WAKTU PENGEMBALIAN TERHADAP KELANCARAN PENGEMBALIAN KREDIT DENGAN KARAKTERISTIK PEMINJAM SEBAGAI VARIABEL MODERASI (Studi kasus pada KSP Kopdit Pintu Air Cabang Lekebai) - Claudia Bara, Jeane; Mitan, Wilhelmina; Yuneti, Katharina (Universitas Nusa Nipa Maumere, 2025)
This study aimed to determine the influence of loan amount, repayment period, and borrower characteristics as a moderating variable on the loan repayment performance at KSP Kopdit Pintu Air Lekebai Branch. The method used in this study was quantitative, employing both primary and secondary data sources. Data were collected through interviews, documentation, and questionnaires, and analyzed using descriptive statistical analysis. The population in this study consisted of cooperative members who were delinquent in loan repayment. The sample was determined using a non-probability sampling technique with saturated sampling. The result showed that the variable affecting the loan repayment performance at KSP Kopdit Pintu Air Lekebai Branch was the repayment period, while the loan amount and borrower characteristics as a moderating variable did not strengthen effect. Furthermore, borrower characteristics as a moderating variable did not stengthen or weaken the effect of loan amount and repayment period on loan repayment performance at KSP Kopdit Pintu Air Lekebai Branch.